2018
DOI: 10.4236/fns.2018.98070
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Frying Oils Supplemented with Vitamin E on Blood Parameters and Growth Performance of Rats

Abstract: This study aimed at investigating effects of frying oils supplemented with vitamin E on blood parameters and growth performance of rats. Three experimental diets containing fresh corn oil or frying oil (FO) with or without vitamin E were fed to Wistar rats over a 90-day. Blood Chemistry, blood parameters (hematocrit and erythrocyte osmotic fragility) and growth performance were determined. Neither FO alone nor vitamin E had any considerable impact on the growth performance. Hematocrit of FO group did not chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The latter had found that the consumption of thermoxidized vegetable oils led to an alteration in platelet function in rats. However, they contradict those of Hamam & Eldalo, (2018). They found that vitamin E supplementation had no impact on the adverse effects caused by frying oil in rats.…”
Section: Effect Of the Different Oil Samples On Liver And Kidney Para...mentioning
confidence: 90%
“…The latter had found that the consumption of thermoxidized vegetable oils led to an alteration in platelet function in rats. However, they contradict those of Hamam & Eldalo, (2018). They found that vitamin E supplementation had no impact on the adverse effects caused by frying oil in rats.…”
Section: Effect Of the Different Oil Samples On Liver And Kidney Para...mentioning
confidence: 90%